Effects of iron and PGPR on antioxidant status and some physiological traits of triticale under different irrigation levels (Bangladesh Journal of Botany, 2020)
A factorial experiment was conducted to study the effects of iron and plant growth promoting rhizobacteria (PGPR) on antioxidant status and some physiological traits of triticale under different irrigation levels. Experimental factors were included irrigation in three levels [(i) normal irrigation (I0) as control; (ii) moderate water limitation (I1) and (iii) severe water limitation (I2)]. Three PGPR levels [(i) no PGPR (P0), (ii) Psedomunas putida (P1), (iii) Azospirillum lipoferum (P2)] and three nano iron oxide levels [(i) without nano iron oxide (F0) as control, (ii) application of 0.3 (F1) and (iii) 0.6 (F2) g/l)]. Results showed that water limitation decreased chlorophyll content, relative water content and grain yield of triticale. Whereas, electrical conductivity, proline content and the activity of catalase (CAT), peroxidase (POD), polyphenol oxidase (PPO) enzymes increased. However, inoculation of plants with PGPR and iron application improved these traits under water limitation condition and normal irrigation. Based on the results, it was concluded that the application of PGPR and iron can be a proper tool for increasing triticale yield under water limitation condition.